One-step, kit-based radiopharmaceuticals for molecular SPECT imaging: a versatile diphosphine chelator for 99mTc radiolabelling of peptides. Issue 44 (27th October 2021) - Hungnes, Ingebjørg N.; Al-Salemee, Fahad; Gawne, Peter J.; Eykyn, Thomas; Atkinson, R. Andrew; Terry, Samantha Y. A.; Clarke, Fiona; Blower, Philip J.; Pringle, Paul G.; Ma, Michelle T.
Abstract : We report a versatile diphosphine platform for 99m Tc radiolabelling of peptides. The diphosphine-peptide conjugate can be radiolabelled with 99m Tc in a single step, and the new radiotracer is capable of receptor-targeted imaging of disease in vivo . Abstract : Radiotracers labelled with technetium-99m ( 99m Tc) enable accessible diagnostic imaging of disease, provided that radiotracer preparation is simple. Whilst 99m Tc radiopharmaceuticals for imaging perfusion are routinely prepared from kits, and regularly used in healthcare, there are no 99m Tc-labelled receptor-targeted radiopharmaceuticals in widespread clinical use. This is in part due to the multistep radiosyntheses required for the latter. We demonstrate that the diphosphine, 2, 3-bis(diphenylphosphino)maleic anhydride (BMA), is an excellent platform for preparation of kit-based, receptor-targeted 99m Tc-labelled radiotracers: its conjugates are simple to prepare and can be easily labelled with 99m Tc using one-step, kit-based protocols. Here, reaction of BMA with the αv β3 -integrin receptor targeted cyclic peptide, Arg-Gly-Asp-DPhe-Lys (RGD), provided the first diphosphine-peptide conjugate, DP-RGD. DP-RGD was incorporated into a "kit", and addition of a saline solution containing 99m TcO4 − to this kit, followed by heating, furnished the radiotracer [ 99m TcO2 (DP-RGD)2 ] + in consistently high radiochemical yields (>90%). The analogous [ReO2 (DP-RGD)2 ] + compound was prepared and characterised, revealing that both [ 99m TcO2 (DP-RGD)2 ] + and [ReO2 (DP-RGD)2 ] + consist of a mixture of cis and trans geometric isomers. Finally, [ 99m TcO2 (DP-RGD)2 ] + exhibited high metabolic stability, and selectively targeted αv β3 -integrin receptors, enabling in vivo SPECT imaging of αv β3 -integrin receptor expression in mice.